Policy Network in Implementing SDGs Program Based on Empowerment of MSMEs (Study on the Ministry of Finance MSME Empowerment Program One Fakfak, West Papua Province) - Ilham Ilham; Muhammad Yunus; Gita Susanti (Program Studi Pendidikan IPS, 2025)
This study analyzes the policy network in the implementation of Sustainable Development Goals (SDGs) through the empowerment of Micro, Small, and Medium Enterprises (MSMEs) in Fakfak Regency, West Papua. It uses a qualitative method with a literature review approach. This study found that the MSME empowerment program facilitated by the Ministry of Finance not only supports the achievement of SDG 8 (Decent Work and Economic Growth), but also contributes to SDG 1 (No Poverty) and SDG 10 (Reduced Inequalities). The results of this study also show the strategic role of MSMEs in strengthening inclusive and sustainable development policy networks. The implementation of the program reflects the dynamics of policy networks, collaborative governance, and multi-stakeholder partnerships, in which various stakeholders work together to support MSME development as an effort to improve welfare and reduce poverty and inequality. The novelty of this research lies in the analysis of the integration of network governance in MSME empowerment programs and their contribution to the achievement of SDGs in West Papua, which has rarely been studied before. This study recommends strengthening the network-based MSME ecosystem as an effective strategy to accelerate the achievement of SDGs while bridging the development gap in Eastern Indonesia.